2000
DOI: 10.4049/jimmunol.165.1.483
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Granuloma Disintegration in Mycobacteria-Infected TNFRp55−/− Mice Is Dependent on T Cells and IL-12

Abstract: Genetically susceptible, TNFRp55 gene-deficient (TNFRp55−/−) mice succumb to infection with Mycobacterium avium. Before their death, M. avium-infected TNFRp55−/− mice develop granulomatous lesions that, in contrast to granulomas in wild-type syngeneic mice, undergo acute disintegration. To determine the factors involved in these events, we depleted T cell subsets or neutralized the inflammatory cytokines IFN-γ, IL-12, or TNF in TNFRp55−/− mice infected i.v. with M. avium. Infected TNFRp55−/− mice treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
54
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 43 publications
8
54
0
5
Order By: Relevance
“…These differences might be due to the genetic background of the animals, since they used CD1 mice, when we infected BALB/c mice. Similarly, Ehlers et al (2000) reported that the TNFRp55-deficient mice succumb to infection with Mycobacterium avium due to high levels of IL12, with necrotic foci in the livers. Gram-negative bacterial septicaemia, with accompanying endogenous endotoxinaemia induces high levels of IL12, IFN-ª and TNF-AE production, contributing much to the pathological findings and lethality observed in experimental toxic shock (Heinzel et al, 1994;Ozmen et al, 1994;Wysocka et al, 1995).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These differences might be due to the genetic background of the animals, since they used CD1 mice, when we infected BALB/c mice. Similarly, Ehlers et al (2000) reported that the TNFRp55-deficient mice succumb to infection with Mycobacterium avium due to high levels of IL12, with necrotic foci in the livers. Gram-negative bacterial septicaemia, with accompanying endogenous endotoxinaemia induces high levels of IL12, IFN-ª and TNF-AE production, contributing much to the pathological findings and lethality observed in experimental toxic shock (Heinzel et al, 1994;Ozmen et al, 1994;Wysocka et al, 1995).…”
Section: Discussionmentioning
confidence: 85%
“…For example, cerebral malaria is thought to be mediated by parasite-induced TNF-AE (Grau et al, 1987). More recently, it has been shown that TNFRp55-deficient mice die after infection with Mycobacterium avium due to high levels of IL12 (Ehlers et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, TNFRp55-KO mice succumbed to challenges with L. monocytogenes, Mycobacterium avium, or M. tuberculosis, showing unaltered or only slightly delayed recruitment of inflammatory cells into infectious lesions (26,27,29). To dissect the ligands involved, studies were also performed in TNF-KO mice and in LT␣-KO mice (31,44).…”
Section: Discussionmentioning
confidence: 99%
“…In combination with the membranebound LT␤, LT␣ binds as the LT␣ 1 ␤ 2 heterotrimer to the LT␤R (16,21,23,24). TNF 3 , LT␣ 3 in concert with the TNFRp55, were shown to be of critical importance for the host defense against intracellularly replicating bacterial pathogens and for the formation and maintenance of fully differentiated granulomas (25)(26)(27)(28)(29)(30)(31). In contrast, the detailed role of the LT␤R and its cognate ligands in antimicrobial resistance and granuloma formation has remained unexplored.…”
mentioning
confidence: 99%
“…It is widely accepted that TNF-␣ 5 is essential for the maintenance of the granuloma and the control of tuberculosis (2). Hosts with a deficiency in TNF-␣ or its receptors are susceptible to mycobacterial infection (3)(4)(5)(6)(7)(8). TNF-␣ controls both the innate and the adaptive arms of the immune response against tuberculosis.…”
mentioning
confidence: 99%